IUCN-SSC Marine Turtle Specialist Group Quarterly Update - Hutchinson, Brian J; Mast, Roderic B; Pilcher, Nicolas J (Marine turtle newsletter, 2009)
As mentioned in our last quarterly update, the MTSG's quadrennial reappointment process is now underway and we have nearly completed the reappointment of all Regional Vice Chairs. The past four years have given us ample opportunity to test and refine the MTSG regional structure, and we have settled on 10 regions that will be used as the basis for the MTSG leadership and membership structures. As in the past, each region will have an appointed Vice Chair (or Chairs) who oversee the regional membership and serves as an important conduit of information between the MTSG members and the Co-Chairs. Listed below are the ten MTSG regions and their Regional Vice Chair or Chairs for the coming quadrennium.